Experimental study of a hybrid platform for high tech equipment protection against earthquake and microvibration. - Xu, Y.L (Earthquake engineering & structural dynamics.)
This paper presents an experimental study to explore the possibility of using a hybrid platform to ensure the functionality of high-tech equipment against microvibration and to protect high tech equipment from damage when an earthquake occurs. A three storey building model and a hybrid platform model were designed and manufactured. The two layer hybrid platform, on which the high tech equipment is placed, was installed on the first floor of the building to work as a passive platform aiming at abating acceleration response of the equipment during an earthquake and functioniong as an actively controlled platform that intends to reduce velocity response of the equipment under a normal working condition. For the hybrid platform working as a passive platform, it was designed in such a way that its stiffness and damping ratio could be changed, whereas for the hybrid platform functioning as an active platform, a piezoelectric actuator with a sub optimal velocity feedback control algorithm was used. A series of shaking table tests, traffic induced vibration tests and impact tests were performed on the building with and without the platform to examine the performance of the hybrid platform. The experimental results demonstrate that the hybrid platform is feasible and effective for high tech equipment protection against earthquake and microvibration.